Developing a Child and Youth Mental Health and Addictions Framework for Yukon as a Foundation for Policy Reform: Engaging Stakeholders Through a Policy and Research Partnership - Mulvale, Gillian; Kutcher, Stanley K.; Meade, Paddy (Patricia) (Health Reform Observer - Observatoire des Réformes de Santé, 2016)
In April 2015 the Yukon Government released a new child and youth mental health and addictions framework (CYMHAF) to improve territory-wide access to basic mental health care and coordination of services for children and families. Yukon’s limited resource base and dispersed population challenges delivery of child and youth mental health and addictions services to small rural communities where needs are often high as a legacy of residential school policies. The objective of CYMHAF is to improve outcomes by identifying and capitalizing on current strengths, and reallocating existing resources to better meet the mental health needs of Yukon youth and families. Access, coordination and quality problems associated with existing services, growing public awareness of mental health issues, and a new national policy framework designed to assist provinces and territories, led Yukon policy makers to partner with researchers to capitalize on a Canadian Institutes of Health Research (CIHR) strategic grant initiative. CYMHAF was based on extensive stakeholder engagement, best evidence and advice from key informants in other jurisdictions, and offers a cascading model of service delivery through which basic mental health care can be provided by existing health and human service workers in communities. These workers will be trained in child and youth mental health competencies, and will have electronic linkages and support to integrated teams of primary care providers who will be located in regional hubs once fully implemented, and to specialists in Whitehorse and out of Territory. Implementation is underway with some training of front line Health and Social Service and First Nations workers, a new mental wellness strategy for Yukon founded on CYMHAF scheduled for release in spring 2016, and may be accelerated by federal government promises of a new Health Accord and a new relationship with indigenous people. Le gouvernement du Yukon a promulgué en avril 2015 une nouvelle approche de la santé mentale et des addictions des ...